Pengembangan Aplikasi Pembelajaran Fun Watch Materi Pengukuran Waktu Siswa Kelas II Sekolah Dasar - Trisnawati, Dina Ayu (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Digital transformation encourages the integration of technology into elementary school mathematics learning, yet the numeracy achievement of Indonesian students remains low. This study aims to develop an Android-based learning application called Fun Watch for time measurement material and to assess its practicality level. The research employs the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects included second-grade students of SD Islam Al-Fattah Semarang City, media experts, material experts, linguists, and teachers. Data were collected through observation, interviews, and questionnaires. The findings show that the Fun Watch application was developed through needs analysis, design based on the Merdeka Curriculum, development using Canva, PowerPoint, iSpring Suite, and Web to APK Builder, as well as limited classroom implementation. The feasibility test results obtained an average percentage of 92.33% (highly feasible), with details of media validation at 95%, material validation at 91.33%, and language validation at 90%. The practicality level based on teacher responses reached 98% (highly practical) and student responses at 95.52% (highly practical). The Fun Watch application proved capable of increasing students' interest, motivation, and active engagement. It is concluded that the Fun Watch application is highly feasible and highly practical to use as a mathematics learning medium for time measurement material in second grade of elementary school